Third-Trimester Lateral Placental Location and Its Association with Adverse Maternal and Perinatal Outcomes in Singleton Pregnancies: A Prospective Observational Study from South India - A, Rathna; Sharma, Nidhi (Journal of Neonatal Surgery, 2025)
Background: Placental location can influence pregnancy outcomes. While anterior and posterior placements are generally benign, lateral placentation has been associated with altered uteroplacental blood flow and adverse outcomes. Data from South India on this association are limited. Objectives: To evaluate whether third-trimester lateral placental location predicts adverse maternal and neonatal outcomes in a South Indian population. Methods: This prospective observational study was conducted at a tertiary care hospital from June 2023 to May 2024, including 300 singleton pregnancies with confirmed placental location on mid- and third-trimester ultrasound. Women with multiple gestations, chronic hypertension, or chronic renal disease were excluded. Placental location was classified as anterior, posterior, fundal, lateral, or low-lying. Maternal and neonatal outcomes were compared across groups. Statistical analysis was performed using Chi-square/Fisher’s exact test and ANOVA, with p < 0.05 considered significant. Results: Lateral placenta in the third trimester was significantly associated with preeclampsia/eclampsia (51.28% vs. 9.96%, p < 0.001), fetal growth restriction (43.59% vs. 6.90%, p < 0.001), antepartum haemorrhage (25.64% vs. 1.92%, p < 0.001), preterm delivery (15.38%, p = 0.0019), and PPROM/PROM (23.08%, p < 0.001). Mean birth weight was lowest in the lateral group (2.34 +/- 0.74 kg, p < 0.001). A history of prior abortions was more frequent in women with lateral placenta (61.54%, p < 0.001). Conclusions: Lateral placental location in the third trimester is associated with higher risks of preeclampsia, growth restriction, antepartum haemorrhage, preterm birth, and low birth weight. Early identification through routine ultrasound could help in targeted antenatal surveillance, especially in resource-limited settings.